New restrictions on possible orders of circulant Hadamard matrices - Leung, Ka Hin (2013)
We obtain several new number theoretic results which improve the field descent method. We use these results to rule out many of the known open cases of the circulant Hadamard matrix conjecture. In particular, the only known open case of the Barker sequence conjecture is settled.